Firm-Specific Factors and the Market Reaction to Dividend Change Announcements: evidence from Europe - Vieira, Elisabete F. Simões
According the dividend signalling hypothesis, it is expected a positive relationship between dividend change announcements and the subsequent share price reactions. However, empirical results are not consensual. This study investigates whether firm-specific factors contribute to explain a negative market reaction to dividend change announcements, contributing to the scarce analysis of firm-specific factors explaining the inverse share price reaction to dividend change announcements. The study applies the panel data approach to three European markets. The results show that the market reaction to dividend change announcements is negatively associated with the firm size. We find that the negative market reaction to dividend increase announcements is associated with firms that have, on average, lower dividend changes and higher growth opportunities. Moreover, the results suggest that a high percentage of dividend negative changes, decreases the likelihood that the market reacts positively to a dividend decrease announcement. Globally, we find some evidence for the dividend signalling hypothesis.